DNA-pools targeted-sequencing as a robust cost-effective method to detect rare variants: application to dilated cardiomyopathy genetic diagnosis - Perret, Claire; Proust, Carole; Esslinger, Ulrike; Ader, Flavie; Haas, Jan; Pruny, Jean-François; Isnard, Richard; Richard, Pascale; Trégouët, David-Alexandre; Charron, Philippe; Cambien, François; Villard, Eric (Clinical genetics, 2023)
Dilated cardiomyopathy (DCM) is a heart disease characterized by left ventricular dilatation and systolic dysfunction. In 30% of cases, pathogenic variants, essentially private to each patient, are identified in at least one of almost 50 reported genes. Thus, while costly, exons capture-based Next Generation Sequencing (NGS) of a targeted gene panel appears as the best strategy to genetically diagnose DCM. Here, we report a NGS strategy applied to pools of 8 DNAs from DCM patients and validate its robustness for rare variants detection at 4-fold reduced cost. Our pipeline uses Freebayes to detect variants with the expected 1/16 allele frequency. From the whole set of detected rare variants in 96 pools we set the variants quality parameters optimizing true positives calling. When compared to simplex DNA sequencing in a shared subset of 50 DNAs, 96% of SNVs/InsDel were accurately identified in pools. Extended to the 384 DNAs included in the study, we detected 100 variants (ACMG class 4 and 5), mostly in well-known morbid gene causing DCM such as TTN, MYH7, FLNC, and TNNT2. To conclude, we report an original pool-sequencing NGS method accurately detecting rare variants. This innovative approach is cost-effective for genetic diagnostic in rare diseases.